Structural Analysis of Natural Products - Přichystal, Jakub; Schug, Kevin A; Lemr, Karel; Novák, Jiří; Havlíček, Vladimír (Analytical chemistry, 2016)
Current mass spectrometry, nuclear magnetic resonance spectroscopy, and X-ray diffraction are presented as structure elucidation tools for analytical chemistry of natural products. Discovering new molecular entities combined with dereplication of known organic compounds represent prerequisites for biological assays and for respective applications as pharmaceuticals or molecular markers. Liquid chromatography is briefly addressed with respect to its use in mass spectrometry- and nuclear magnetic resonance-based metabolomics studies.